Gestión administrativa y su incidencia en los servicios financieros de la caja de ahorro interna docente de la universidad técnica estatal de Quevedo “uteq”, año 2023 - Intriago Reyes, Jessenia Paola (2025)
The present study aimed to evaluate the impact of administrative management on the financial services of the Internal Savings Fund for Faculty of the Technical State University of Quevedo (UTEQ) during the year 2023. The methodology employed was a mixed-methods approach with a descriptive and correlational design. Structured surveys were administered to 80 faculty members affiliated with the Savings Fund, in addition to interviews conducted with its administrative staff. The data were analyzed quantitatively using descriptive and inferential statistics, including Pearson and Spearman correlations, and qualitatively through content analysis. Among the main findings, the most frequently used financial services were scheduled savings and standard loans, both of which received high levels of acceptance among members. Overall satisfaction with the services was high, with 65% reporting being "very satisfied" and 35% "satisfied." The statistical correlation between administrative management and the quality of financial services was significantly positive (r = 0.892, p < 0.01), supporting the hypothesis that effective management directly influences the efficiency and perception of the services provided. In conclusion, the administrative management of UTEQ’s Internal Faculty Savings Fund has a direct and positive impact on the quality of its financial services. However, it is recommended to implement more comprehensive and digitized management systems to enable more rigorous monitoring of its operational and financial processes.